Cuentos sobrecogedores : antología (Andrés Bello)
Antología que incluye cuentos de: Edgard Allan Poe, Guy de Maupassant, Emilia Pardo Bazán, Osar Wilde, Anton Chejov, O'Henry, Joaquín Dicenta, W.W. Jacobs, Horacio Quiroga, Stefan Zweig, Francisco Coloane.